Math, asked by shivangisharma14, 1 year ago

Hello pls solve the above question ​

Attachments:

Answers

Answered by Anonymous
1

x = a and y = b

Check the attached image.

Attachments:
Answered by Anonymous
7

GIVEN :

 \frac{x}{a}  -  \frac{y}{b}  = 0............(i) \\ ax  + by =  {a}^{2}  +  {b}^{2} ..........(ii)

SOLUTION :

★Taking eq (i) ★

 \frac{x}{a}  -  \frac{y}{b}  = 0 \\  \implies \frac{xb - ay}{ab}  = 0 \\  \implies \: xb -  ay = 0 ...........(i)

Multiply a with eq(i) and b with eq(ii)

axb -  {a}^{2} y = 0.......(i) \\  axb +  {b}^{2} y =  {a}^{2} b +  {b}^{3} ........(ii)

By elimination :-

axb -  {a}^{2} y = 0 \\ axb +  {b}^{2} y =  {a}^{2} b +  {b}^{3}

(-). (-). (-)

_____________________________

- a²y - b²y = -a²b - b³

→ -y (a² + b²) = - b(a² +b²)

→ - y = - b

→. y = b

Putting y = b in eq(i)✪

xb - ay = 0

→ xb - ab = 0

→ xb = ab

→ x = ab/b

x = a

Therefore ,

x = a

y = b

_________________________

MORE INFORMATION:

Algebraic Identity :-

★(a+b)² = a²+2ab+b²

★(a-b)² = a²-2ab+b²

★ a²- b² = (a+b)(a-b)

★ a²+b² = (a+b)²-2ab

★(a+b)²+(a-b)² = 2(a²+b²)

★(a+b)²-(a-b)² = 4ab

__________________________

Similar questions